Systematic correlation of morphologic alterations and retinal function in eyes with uveitis-associated cystoid macular oedema during development, resolution and relapse. Issue 10 (2nd August 2013) - Munk, Marion R; Kiss, Christopher G; Steiner, Irene; Sulzbacher, Florian; Roberts, Phillipp; Kroh, Maria; Montuoro, Alessio; Simader, Christian; Schmidt-Erfurth, Ursula
Abstract : Purpose: To evaluate morphological changes due to uveitis-associated cystoid macular oedema (uvCME) and their impact on central retinal sensitivity (CRS) before and after intravitreal triamcinolone-acetonide (IVTA). Methods: 28 eyes with uvCME were examined with microperimetry and spectral-domain optical-coherence-tomography (SD-OCT) before and after IVTA. Microperimetry-maps were superimposed on SD-OCT and morphological-alterations were correlated point to point with CRS and followed-up for 3 months. The effects of morphological-alterations on CRS over time were evaluated with a linear mixed-model. Results: Mean-CRS increased significantly after IVTA (p=0.009). Proportion of cysts correlated negatively with corresponding CRS (estimate/95% CI −3.8dB/−6.6 to −0.9, p=0.011). Proportion of diffuse macular-oedema (DifME) had no significant effect on mean-CRS (−0.76dB/−4.9 to 3.3, p=0.71). The proportion of serous retinal detachment (SRD) had a borderline significant effect on mean-CRS (−9.5dB/−19.1 to 0.1, p=0.052), however the initial presence of SRD at baseline had no significant negative effect on mean-CRS (−1.3dB/−4.9 to 2.3, p=0.46). Patients with epiretinal-membrane showed lower mean-CRS than patients without (−3.3dB/−6.5 to −0.008, p=0.05). The lowest percentage of morphological-alterations was achieved 30 days post IVTA concordant to best visual-acuity (logMAR 0.16±0.26), while best mean-CRS was achieved 90 days post IVTA (16.9±1.8dB). Fixation-stability showed no significant improvement. Conclusions: UvCME Morphological-alterations were associated with specific CRS-decreases. DifME showed no significant- and SRD only a borderline effect on mean-CRS, which implicates that their presence should be considered when interpreting SD-OCT and making treatment-decisions.